Efeito do monossialogangliosídeo GM1 sobre as alterações comportamentais, euroquímicas e eletrográficas induzidas pelo ácido glutárico e nas defesas antioxidantes no SNC de ratos - Fighera, Michele Rechia (2006)
Monosialoganglioside (GM1) is a component of most cell membranes and is thought to play a role in development, recognition and cellular differentiation. Furthermore, GM1 is a neuroprotective agent that has been reported to scavenge free radicals generated during reperfusion and to protect receptors and enzymes from oxidative damage. In the present study we investigate the effect of GM1 on the catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities, on the spontaneous chemiluminescence and total radical-trapping potential (TRAP) in cortex of rats ex vivo and in vitro. Systemic GM1 administration (50 mg/kg, i.p.; twice) reduced spontaneous chemiluminescence and increased CAT activity ex vivo. On the other hand, GM1 (103-104 nM) reduced CAT activity in vitro. The other parameters were not affected by GM1 administration. These findings agree with the view that the antioxidant action of GM1 is not due to an intrinsic antioxidant activity of this glycolipid, but due to a secondary decrease of reactive species generation and/or increase of antioxidant defenses. Moreover, we evaluated whether GM1 could have a neuroprotective action on the experimental model of glutaric acidemia, an inherited metabolic disorder characterized by glutaric acid (GA) accumulation and neurological dysfunction, as striatal degeneration and convulsion. The systemic GM1 administration (50 mg/kg, i.p. twice) protected against the convulsions, oxidative damage markers increase (total protein carbonylation and thiobarbituric acid-reactive substances - TBARS) production and Na+,K+-ATPase activity inhibition induced by GA (4 mol/ 2 l) in striatum of rats. Furthermore, convulsive episodes induced by GA strongly correlated with Na+,K+-ATPase activity inhibition in the injected striatum, but not with oxidative stress marker measures. In addition, GM1 (50-200 M) protected against Na+,K+-ATPase inhibition induced by GA (6 mM), but not against oxidative damage in vitro. Intrastriatal administration of muscimol (46 pmol/striatum), a GABAA receptor agonist, but not glutamatergic receptor antagonists MK-801 (3 nmol/striatum) and DNQX (8 nmol/striatum), prevented GA-induced convulsions and inhibition of Na+,K+-ATPase activity. The protection of GM1 and muscimol against GA-induced seizures strongly correlated with Na+,K+-ATPase activity maintenance in the injected striatum with GA. Since GM1 and muscimol prevented neurotoxic effects induced by GA, we investigated the GM1 action after intrastriatal administration of pentylenetetrazole (PTZ), a GABAA receptor antagonist. GM1 treatment prevented seizures, Na+,K+-ATPase inhibition, and increase of TBARS and protein carbonyl induced by PTZ (1.8 mol/striatum) in the rats striatum. Furthermore, these data suggest that Na+,K+-ATPase and GABAA receptor-mediated mechanisms may play important roles in GA-induced seizures and in their prevention by GM1.